A gender wise correlation analysis between glycated hemoglobin level and estimated glomerular filtration rate among type 2 diabetes patients - Leena, Chalissery Ouseph; Ajith, Thekkuttuparambil Ananthanarayanan; Vijayasimha, Mulavagili; Sah, Ashok Kumar (International Journal of Advances in Medicine, 2021)
Background: Studies found inconsistent relationship between glycated hemoglobin (HbA1C) and estimated glomerular filtration rate (eGFR) in diabetes. Hence, population based studies are warranted. This study was aimed to find out the prevalence of good glycemic control and correlation of HbA1c level with eGFR in male and female type 2 diabetes patients. Methods: A cross sectional study was designed among type 2 diabetes patients. Medical records of patients’ in the inclusion criteria were abstracted for demographic characteristics, HbA1c and serum creatinine level. Patients were grouped into male and female and further sub grouped as with or without good glycemic control (HbA1c ≤ 7%). Data were statistically analyzed. Results: A total of 465 diabetes patients (186 males and 279 females) were included. Among the total, more female patients were in good glycemic (p=0.0008) control. Gender wise comparison showed that HbA1c level was statistically significant between male and female patients in age groups below 60 years (p<0.05). HbA1c level, at >7%, showed an inverse correlation with eGFR in both male (r=- 0.3208, p=0.0008) and female patients (r =-0.3680, p<0.0001). For every 1% rise in HbA1c, eGFR declined by 10 ml/min/1.73 m2 in males and 13 ml/min/1.73 m2 in females. Conclusions: More female patients were in good glycemic control. HbA1c level above 7% showed an inverse correlation with eGFR in both male and female patients. For every 1% rise in HbA1c, the eGFR declined by 10 ml/min/1.73 m2 in male and 13 ml/min/1.73 m2 in female patients.